PM10 AND PM2,5 TEMPORAL VARIATIONS AND THE EFFECT OF METEOROLOGICAL FACTORS IN DKI JAKARTA 2018 â 2020 - Khasanah, Nurfian
DKI Jakarta is a densely populated city and has high industrial, transportation, and domestic activities causing air pollution problems. Particulates have negative impacts on health and the environment, therefore it is important to understand their temporal variations. Based on 2018- 2020 data, diurnal variations PM10 concentration showed general patterns rises in the early morning and reached the highest concentration after dawnbefore and decreasing in to the lowest point in the evening. PM2,5 generally had the highest concentration in the early hours of the morning until past dawn and began to decrease to the lowest levels in the evening. Both PM10 and PM2,5 concentration did not meet annual ambient air quality standard in 2018-2020. For the daily average, the percentage of AAQS violations for PM10 were 15%, 39%, 21%, 47%, and 24% for DKI 1, DKI 2, DKI 3, DKI 4, and DKI 5, respectively. The percentage of AAQS violations for PM2,5 were 12%, 34%, 24%, 17%, and 25% at AirNow 1, AirNow 2, DKI 1, DKI 2, and DKI 3, respectively. The highest monthly variations showed that the highest concentration were found during the dry season (June-July-August) and low concentration were found during the rainy season (December-January-February). Particulates have low to moderate (PM10= 0,26-0,47 & PM2,5= 0,28-0,5) positive correlation with temperature, moderate to strong significantly negative correlations were found with humidity (PM10= 0,45- 0,67 & PM2,5= 0,45-0,63), wind speed showed low to moderate significantly negative correlation (PM10= 0,24-0,59 & PM2,5= 0,22-0,5), except wind speed in PM10-DKI 4 and PM2,5-DKI 3.